Halal Certification Revocation and Market Withdrawal for Hazardous Food Products - Salma Naila Wandani; Dwi Desi Yayi Tarina (Al-Risalah, 2026)
This research discusses how to withdraw distribution permits and revoke halal certification for food products containing harmful chemicals through the case study of Roti Okko. This product was found to have banned extra ingredients, specifically sodium dehydroacetate, which breaks food safety laws and halal product guarantees. The study examines the legal aspects through statutory and conceptual methods, focusing on the dual enforcement by BPOM and BPJPH for food products with dangerous chemicals, using Roti Okko as a case example. The problem statement looks closely at how the two authorities responded to this double violation and its legal implications. The main findings show a clear division of authority. BPOM can withdraw distribution permits and remove products from sale due to food safety violations. At the same time, BPJPH can revoke halal certification when the ingredient composition does not match the registration details. This process is crucial for protecting consumers in terms of health and religious beliefs. The violation leads to serious legal consequences, including administrative penalties like the withdrawal or revocation of permits, civil claims for compensation, and possible criminal charges. Producers may also have to dispose of products in B3 waste facilities, highlighting the high costs of failing to comply. Practically, these findings suggest the need for better alignment of procedures and improved data sharing between BPOM and BPJPH for policymakers. They also stress the importance for producers to enhance their internal Quality Control systems to guard against various legal risks and to affirm consumer legal protection.